Family Farming Systems in Northern Central Cameroon: Challenges and Prospects for Food Security - Marie Chimi, Pierre; Armand Mala, William; Manga Essouma, François; Karimou Ngamsou, Abdel; Hermann Matick, John; Louis Fobane, Jean; Preasious Funwi, Forbi; Kouoguem Kamdem, Michele Elodie; Feunang Nganmegni, Lethicia Flavine; Martin Bell, Joseph (European Scientific Journal, ESJ, 2023)
If family farming is supported, it can serve as a foundation for growth and food security. One of Cameroon’s biggest development challenges is still food insecurity. Therefore, the purpose of this study was to investigate the situation and key determinants of food security in the northern forest-savanna transition zone of the Central Cameroon Region. To do this, 180 family farmers from Mbangassina, Ntui, Batchenga, and Obala participated in a survey and field observations (January-March 2020; March-May 2021, and July-September 2021). According to this survey and these findings, the useful agricultural area is 4.55 ± 0.21 hectares. Cocoa, yam, cassava, maize, plantain, sweet potato, and peanut are the principal crops mentioned. With a mixed workforce, the vast majority of agricultural work is performed manually (machetes, daba, etc). (Family and external). Seven significant challenges face family farming in these areas: poor market organization, bad road/track conditions, a lack of inputs, seasonal uncertainties/rainfall deficits, challenging access to irrigation, unstable land tenure, challenging access to credit, and challenging access to agricultural equipment. Each community faces unique challenges. The family agricultural industry, which these people rely on for their food security, needs to be saved to overcome these obstacles. According to the findings, expanding access to financial and commercial services will help agricultural operations in the study area increase food security. This will be in line with initiatives made by both governmental and non-governmental organizations to advance agricultural technologies as a way to address the issue of food insecurity.